Competition Policies for the Telecommunications Industry in Korea - Nam, Il Chong (Korea Development Institute, 1997)
In the past fifteen years or so, the world has been witnessing a fundamental change in the way telecommunications industry operates. For many countries, introducing competition into the telecommunications industry has proved to be much more than allowing more firms into the industry. It required the transformation of a monopolistic government business into a competitive industry, which in turn demanded the redefinition of the role of the government, creation of a proper regulatory regime, a new set of rules governing who could participate in what parts of the new business opportunity, rules to set rates and access charges, and so on. The process of transformation in Korea has not been always orderly and is still unfolding. The Korean experience seems to present a unique example of deregulation of the telecommunications industry. First, the role of the government has not been clearly redefined. The government opted to allow some private firms into the telecommunications industry while at the same time retaining control of Korea Telecom (KT) that had been the monopolistic public enterprise before deregulation. Thus, the government put itself in a position to provide services in competition with private entrants. This is in sharp contrast to the comparable cases in the U.K. or New Zealand. Second, the regulatory regime has not changed much from the days of government monopoly. Third, the omnipresent industrial policies, whose objectives are sometimes ambiguous, have allowed the government to intervene in the industry extensively during the whole process. The purpose of this paper is to evaluate the deregulation of the telecommunications industry in Korea and to make some policy suggestions aimed at improving the efficiency. We also attempt to explain why the deregulation process has followed the actual outcomes. Our analysis will also shed some light on how industrial policies affect competition policies in general in Korea. After summarizing major events in the deregulation process, we will analyze the effects of several key policies that have been employed by the Korean government, from the policy toward KT, to the policy on entry, rates, access charges, and on the regulatory regime. We also discuss the industrial policy of promoting the equipment manufacturing industry. We argue that the telecommunications industry in Korea is not really a competitive industry, based upon the analysis of the past and current policies chosen by the Korean government. The paper is organized as follows: In section 2, we summarize the history of the industry from the government monopoly to the current state. In sections 3, we evaluate the deregulation process and the current policies toward the telecommunications industry in Korea. This section focuses on the effects of past and current policies regarding rivatization, entry, rates, access charges, and the regulatory regime. Section 4 draws conclusions.